Prerequisites of Third-Person Pronoun Use in Monolingual and Bilingual Children With Autism and Typical Language Development - Meir, Natalia; Novogrodsky, Rama (Frontiers in Psychology, 2019)
The current study investigated the production of third-person subject and object pronouns in monolingual and bilingual children with High Functioning Autism (HFA) and typical language development (TLD). Furthermore, it evaluated the underlying linguistic and nonlinguistic prerequisites of pronoun use, by assessing the role of morpho-syntactic skills, Theory of Mind abilities, working memory and inhibition on pronoun use. A total of 85 children aged 4;6-9;2 participated in four groups: 27 children with HFA (14 monolingual (monoHFA) and 13 bilingual (biHFA)), and 58 children with TLD (28 monolingual (monoTLD) and 30 bilingual (biTLD)). All children spoke Hebrew and the bilingual children spoke Russian as their Heritage Language. Third-person subject and object pronouns were elicited in Hebrew. The results yielded no effect of bilingualism and a robust effect of HFA for the use of pronouns. Bilingual Russian-Hebrew speaking children paired up with their monolingual Hebrew-speaking peers in pronominal use in Hebrew. Monolingual and bilingual children with TLD showed nearly ceiling performance on pronoun use. The facilitative effect of pronominal acquisition in Hebrew among bilingual children was attributed to similarities in the pronominal systems of the two languages of bilingual children. Age was found to be a predictive factor of pronoun use in children with TLD. Conversely, children with HFA had a lower rate of pronoun production compared to the TLD groups. Both third-person subject and object pronouns were largely predicted by morpho-syntactic abilities of children with HFA. In addition, subject pronoun use was predicted by ToM skills and working memory confirming that pronoun use is a complex phenomenon, which requires integration of multiple linguistic and nonlinguistic components. To conclude, our findings suggest that morpho-syntactic development is a prerequisite for third-person subject and object pronoun use in children with HFA, and ToM and working memory are involved in third-person subject pronoun use. In addition, we show that pronoun use is not compromised by dual language exposure in children with TLD and with HFA.